Development of a multisite model for Ni(II) ion in solution from thermodynamic and kinetic data. Issue 21 (30th May 2017) - Masetti, Matteo; Musiani, Francesco; Bernetti, Mattia; Falchi, Federico; Cavalli, Andrea; Ciurli, Stefano; Recanatini, Maurizio
Abstract : Force‐field parameters are developed for a multisite model of Ni(II) ions to be used in molecular dynamics simulations combined to enhanced sampling methods. The performances of two charge‐partitioning schemes are validated by taking into account structural, thermodynamic, and kinetic observables. One of the two models, featuring partial charges on the dummy atoms only, matches both Ni(II) free energy of solvation and water exchange rates. Such model is particularly suited to study complexation events at a fully dynamic description. © 2017 Wiley Periodicals, Inc. Abstract : Force‐field parameterization of transition metal ions is a challenging task. While conventional "spherical" models are widely employed in molecular dynamics simulations, they are also severely limited by their simple geometry. This work shows a parameterization of the Nickel(II) ion using a more flexible multisite model. The parameter space is exhaustively scanned taking also into account two different charge‐partitioning schemes. The fittest models are then validated for their ability to reproduce ion‐water exchange rates.